Healthcare Networks and comprehensive care for people living with HIV and AIDS - dos Santos, Rosana; Apostólico, Maíra Rosa (O Mundo da Saúde, 2019)
The chronic scenario of AIDS requires managing patient stability using antiretrovirals. Thus, some Brazilian municipalities the process of decentralization of care for Primary Health Care began. Clarity about the distribution of health resources in a territory is essential to identify the possibility of decentralized work. The objective of this study was to characterize the spatial distribution of municipal institutions of Primary Health Care and others in the city of São Paulo, that would potentially tend to people living with HIV. An exploratory study was performed using a geoprocessing technique with an online tool of data from secondary sources. The Southern and Southeastern regions are the most populous and record the largest number of diagnoses and health resources, among the 817 service centers mapped in the municipality. It was observed that periphery areas do not have specialized services. The Central region has the best proportion of population and basic units, followed by the Western, Southeastern, Northern, Eastern and Southern. Regarding the proportion of people with HIV and Primary Care Centers, the same classification is repeated, despite the discrepancy of the Central region to the rest. It is concluded that the spatial distribution of municipal health institutions can be considered a potential start of a decentralization process, although there are regions with less health coverage. However, it is necessary to invest in professional qualification and physical restructuring.